Corporate Social Responsibility (CSR): Assessing the Participant Perception Towards the Implementation of Sciencexplorer Programme - Muhamad, Aida; Aryanie Bahrudin, Ida; Faezah Adan, Nor; Ezree Abdullah, Mohd; Sufi Bin Roslan, Muhammad; Mohd Adnan, Raudah; Md Amin, Zulkarnain (International Journal of Engineering and Technology, 2018)
Science, Technology, Engineering and Mathematics (STEM) subjects have always been complex subjects for school children as many experienced difficulty and complexity in grasping the basic conceptual knowledge. Therefore, Centre for Diploma Studies (CeDS) of Universiti Tun Hussein Onn Malaysia (UTHM) is moving forward to achieve sustainable development for society by pursuing Corporate Social Responsibility (CSR) through National Blue Ocean Strategy 4 (NBOS 4) initiatives. As a member of the society, CeDS try to ensure that the society will acquire the benefit of CeDS business activities as a whole.. ScienceXplorer programme had been implemented to attract primary school students in learning science. ScienceXplorer is a programme that basically implementing the concept of learning by doing. This study was performed to assess participant perception towards the implementation of ScienceXplorer. A self-completion questionnaire had been designed with a series of Likert scale questions that organized to gather participantsâ€™ perceptions of participating ScienceXplorer. The questionnaire had been designed using Kirk Patrick Evaluation Model. There were 148 participants from three primary schools took part in this study. In this scope of study, ScienceXplorer participants rated very high in terms of reflection, knowledge and skill, changes in behaviour and aspiration.Â Â